Nurcholish Madjid’s Perspective on the Isnad Tradition in the Transmission of Knowledge within Indonesian Pesantren - Arhan; Mubarok, Mim Maulana; Yusuf, Kamal (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the perspective of Nurcholish Madjid on the tradition of isnad in the transmission of Islamic knowledge within Indonesian pesantren. The isnad tradition functions to preserve the continuity, validity, and authority of Islamic scholarship; however, modernity and digitalization have transformed patterns of knowledge transmission and religious authority. This study aims to analyze the concept of isnad in pesantren, Nurcholish Madjid’s views on Islamic intellectual tradition, and the relevance of sanad in contemporary Islamic education. The research employs a qualitative approach using descriptive-analytical library research. Data were collected from the works of Nurcholish Madjid and related literature on pesantren and Islamic scholarly sanad. The findings indicate that the isnad functions not only as a chain of knowledge transmission but also as a system for shaping intellectual ethics and legitimizing religious authority. From Nurcholish Madjid’s perspective, sanad should be understood epistemologically and morally, rather than merely as a genealogical formality. In the digital era, the tradition of isnad remains relevant as an instrument for validating religious knowledge and strengthening religious moderation.